Evaluation of early and mid-late sugarcane (Saccharum officinarum) varieties for yield of millable cane and quality of jaggery - TIWARI, R J; CHATTERJEE, A (The Indian Journal of Agricultural Sciences, 2013)
A field experiment was conducted during 1993-94 to 1995-96 with 12 promising varieties of sugarcane (Saccharumofficinarum L.) to evaluate the yield of mill able cane and quality of jaggery. Sugarcane cv 'CoJN 86-141' recordedmaximum diameter (2.98 cm), height (287 cm), millable cane yield (99.0 tonnes/ha), brix (21.2%), sucrose (19.64 %),sugar recovery (12.20 %),jaggery yield (14.95 tonnes/ha) and jaggery recovery (15.1 %), whereas 'CoC 671' recordedhighestjaggery quality.